Realize a dialogical and transformative Christian education in the context of pluralism - Udur Ernita Aritonang; Dirk Roy Kolibu (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This article examines the urgency of dialogical and transformative Christian Religious Education (PAK) in the context of a pluralistic society. It examines the thoughts of Paul F. Knitter and Pahala J. Simanjuntak as representatives of the theology of interreligious dialogue and prophetic educational practice in Indonesia. Knitter's idea of ​​mutual transformation in the theology of religions offers a new paradigm for the existence of Christian faith amidst plurality, while Simanjuntak's approach emphasizes the importance of contextual, liberating, and social justice-oriented Christian education. This article employs a qualitative approach with a critical-hermeneutic analysis of the main works of both figures, and examines them within the framework of Paulo Freire's pluralistic theology of religions and critical pedagogy. The results demonstrate that the integration of dialogical theology and transformative pedagogy enables the realization of PAK that not only maintains the authentic identity of the Christian faith but also opens itself to interreligious dynamics and global humanitarian challenges. Thus, Christian Education can become a field of liberatory practice that brings together spirituality, critical reflection, and social transformation in the light of the Gospel.